Resection of Foramen Magnum Meningioma through Modified Far Lateral Approach: Surgical Principles and Technical Nuances - Narayan, Vinayak; Jumah, Fareed; Nanda, Anil (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objectives Safe maximal resection is the basic principle of cranial base surgery and the grade of resection is an important factor influencing the prognostic outcome. This operative video highlights the surgical principles and technical nuances in the microsurgical resection of foramen magnum meningioma (FMM).Case Description The surgery was performed in a 45-year-old lady who presented with hoarseness of voice and spastic quadriparesis (grade 4/5). On imaging, FMM with mass effect on brainstem and spinal cord was identified. The tumor was gross totally resected through modified far lateral approach with minimal occipital condyle drilling. This video demonstrates the surgical techniques of tumor resection including early devascularization, operating in the arachnoid plane to dissect the neurovascular structures, piecemeal decompression, sharp dissection to separate tumor from lower cranial nerves (LCN), identifying the brainstem veins, and resecting the lesion from tumor–brainstem interface. Postoperatively, she had significant neurological improvement and the magnetic resonance imaging revealed excellent radiological outcome (Figs. 1 and 2).Conclusion The surgery of FMM is challenging due to the deep surgical corridor, critical location, close proximity with various neurovascular structures, firm consistency, and high vascularity of the tumor. The modified far lateral approach by preserving the occipital condyle may prevent the postoperative incidence of craniovertebral junction instability. The key operative principles to achieve the best surgical outcome include careful dissection along the arachnoid plane, gentle handling of cranial nerves, veins, and perforator vessels, avoidance of traction on brainstem and spinal cord, intraoperative neurophysiological monitoring, proper hemostasis, and meticulous dural closure.The link to the video can be found at: https://youtu.be/1qvAeUmNIUw.
Keywords: meningioma; modified far lateral; foramen magnum; resection; approach